Web-Based Raw Material Inventory Forecasting System : Using Double Exponential Smoothing Method In Selera Baru Bakery - Malika, Melda; Suseno, Endra; Mirantika, Nita (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2024)
Controlling raw material inventory is important in every production process, but Selera Baru Bakery has not received control over the raw material inventory procurement process, so business owner does not know when the right time to procure raw materials is. This causes bread production to be carried out in accordance with the availability of existing raw materials when the production process is carried out not based on sales needs. The production process that is not in accordance with these needs results in a shortage or excess stock so that the bread is moldy and not suitable for sale. Based on this condition, research is conducted using the Double Exponential Smoothing method with PHP programming language and MySQL uses database. System design uses UML and system development uses Waterfall, based on the categories of wheat raw materials, flour, yeast, sugar, eggs and margarine with alpha parameter testing of 0.2 showing effectiveness in using the Double Exponential Smoothing method with a MAPE value of less than 10%, this proves that the forecasting results are effective and accurate in controlling the raw material inventory procurement process in Selera Baru Bakery.